Translating English-language Christian-themed fiction in Taiwan (2000-) - Liu, Ya-chun (2020)
This product- and process-oriented study looks into the translingual and transcultural phenomena surrounding the introduction of English-language Christian-themed literature into Taiwan after the year 2000. The texts chosen for this study are C. S. Lewis’ The Chronicles of Narnia, Marilynne Robinson’s Gilead, and William P. Young’s The Shack. The empirical data for this research contains the translated texts and their source texts, various paratextual materials, my own observations, and the information obtained from my interviews and correspondence with translation agents in Taiwan. Polysystem theory is used to analyse my findings regarding the interaction of relevant cultural systems, such as the Christian and secular cultural systems in Taiwan and the U.S. My case studies show that the introduction of Christian-themed fiction from the Anglophone contexts into the Taiwanese context can be understood as systemic functioning. In the theoretical aspect, my discussion illustrates the continued usefulness of the polysystem approach for investigating translation phenomena if it is integrated with other theories to take into account of the weaknesses that criticism has pointed out: mainly its downplay of agents (or, institution) and its subjectiveness. I tackle these limitations by borrowing theoretical elements from two of the most known social theories in translation studies: Pierre Bourdieu’s sociology of culture featuring ‘field’, ‘habitus’, and ‘capital’, and Niklas Luhmann’s social systems theory. This study suggests that polysystem theory can be applied to examine literary and cultural phenomena in which the institution plays a major role, especially when the institutional efforts tend to adhere to a certain belief system. However, to weaken the mechanical tendency hinted by system-based theories, it would be helpful to incorporate Bourdieu’s idea of habitus into the system-oriented theoretical framework. Luhmann’s theorisation of social systems helps to strengthen my point on the structuralisation and self-containedness of the Christian literary polysystem and also enables me to critically reflect on the vantage points from which the systems are examined and described.